Positive effects of alternative cropping systems on terrestrial Oligochaeta (Clitellata, Annelida) - Francesca Ricci; Laure Bentze; David Montagne; Sabine Houot; Celine Pelosi (Soil Organisms, 2015)
Agricultural intensification has reduced soil biodiversity in cultivated fields. Alternative cropping systems have been implemented to limit the harmful environmental effects of intensive conventional systems. This study aims at (i) assessing the impact of alternative systems on abundance and biomass of earthworms and enchytraeids, which are involved in key agro-ecological functions, and (ii) investigating the relationship between these soil organisms, under field conditions. Field data were collected in spring 2014 in two long-term agricultural sites near Paris, France. In Site 1, two types of organic amendments i.e. animal manure (MAN) and composted sludge (SLU) were compared to a control system (CONT) without organic fertilization. In Site 2, four different cropping systems were compared: a conventional (CONV), an integrated (INT), an organic (ORG) and a living mulch-based cropping system (LIV). They differed mainly in soil tillage, pesticide and fertilizer use, crop rotation and  crop biomass production. In both sites, higher earthworm abundance was found in the alternative systems except in the INT system i.e. SLU, MAN vs CONT and LIV, ORG vs CONV, even if differences were not always significant. For enchytraeids, we found no significant effect of organic amendments but a higher abundance in LIV and ORG systems than in CONV and INT systems in Site 2. Positive effects of alternative systems on earthworm and enchytraeid communities could be explained by the organic amendments in Site 1 and the permanent plant cover, the absence of pesticide use and tillage and the crop rotations in Site 2. Finally, no significant correlation was found between enchytraeid and earthworm abundance or biomass. We concluded that under environmental favorable conditions, earthworms and enchytraeids could coexist without competitive exclusion.